Salinity tolerant Aedes aegypti and Ae. albopictus—Infection with dengue virus and contribution to dengue transmission in a coastal peninsula - Surendran, S.N.; Veluppillai, T.; Eswaramohan, T.; Sivabalakrishnan, K.; Noordeen, F.; Ramasamy, R. (University of Jaffna, 2018)
Background & objectives: Aedes aegypti and Ae. albopictus are major arboviral vectors that are considered to lay eggs, and undergo preimaginal development only in fresh water collections. However, recently they have been also shown to develop in coastal brackish water habitats. The ability of the biologically variant salinity-tolerant Aedes vectors to transmit arboviral diseases is unknown. We therefore, investigated the infection of salinity-tolerant Aedes mosquitoes with dengue virus (DENV) and analysed dengue incidence and rainfall data to assess the contribution of salinity-tolerant Aedes vectors to dengue transmission in the coastal Jaffna peninsula in Sri Lanka. Methods: Brackish and fresh water developing female Ae. aegypti and Ae. albopictus were tested for their ability to become infected with DENV through in vitro blood feeding and then transmit DENV vertically to their progeny. An immunochromatographic test for the NS1 antigen was used to detect DENV. Temporal variation in dengue incidence in relation to rainfall was analysed for the peninsula and other parts of Sri Lanka. Results: Aedes aegypti and Ae. albopictus developing in brackish water, became infected with DENV through in vitro blood feeding and the infected mosquitoes were able to vertically transmit DENV to their progeny. Monsoonal rainfall was the discernible factor responsible for the seasonal increase in dengue incidence in the peninsula and elsewhere in Sri Lanka. Interpretation & conclusion: Fresh water Aedes vectors are main contributors to the increased dengue incidence that typically follows monsoons in the Jaffna peninsula and elsewhere in Sri Lanka. It is possible however, that brackish water-developing Aedes constitute a perennial reservoir for DENV to maintain a basal level of dengue transmission in coastal areas of the peninsula during the dry season, and this supports increased transmission when monsoonal rains expand populations of fresh water Aedes
Keywords: aedes aegypti; ae. albopictus; brackish water larval habitats; coastal zones; dengue transmission and rainfall; jaffna peninsula; salinity tolerant mosquito vectors; sri lanka